PENGARUH INFORMASI AKUNTANSI TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2011 - Pangaribuan, Jonner (UNIKA Santo Thomas, 2013)
Investors intentionally want to get profit contionously.In stock market profit is gained from price differnce of buying and seling price, besides dividend. Theoritical approach (fundamental approach it is concluded that stock price is influenced by accounting infornatio.. In this research it is intended to find out whether the four fundamental facorscan can explain the stock price change. The selected four fundamental factors are return on equity, debt equuity ratio , book value, dan total asset turnover..The result shows that the four fundamental factors can not explain the price change of Food and Beverages companies stocks.